Payout Policy Tax Clienteles, Ex‐dividend Day Stock Prices and Trading Behavior in Germany: The Case of the 2001 Tax Reform. (25th April 2013) - Haesner, Christian; Schanz, Deborah
Abstract This paper examines the impact of the German 2001 tax reform, where Germany switched from a full imputation system to a classical system. Theory suggests that both price drop ratios and trading volume decrease following the reform. We document a significant reduction in the valuation of net dividends–in particular for high dividend yield stocks–and weakening payout policy tax clienteles. Ex‐dividend day returns are likely to be driven by short‐term traders. Though the reform removed incentives for cross‐border dividend stripping and reduced tax heterogeneity among investors, we show that the high trading volume around ex‐dividend days persists.